PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PEGADAIAN (PERSERO) CABANG PASAR RUMPUT - Niken Dayu Listian; Edi Komara (Journal of Accounting, Management and Islamic Economics, 2025)
This research aims to analyze the effect of work motivation and work discipline on employee performance at PT Pegadaian (Persero) Pasar Rumput Branch. The study uses a quantitative method with data collected through a structured questionnaire distributed to 35 employees. Multiple linear regression analysis is applied to examine the relationship among variables. The findings reveal that both work motivation and discipline simultaneously have a significant influence on performance. However, work discipline has a more dominant effect. The coefficient of determination (R2) indicates that 69.5% of employee performance can be explained by the two variables. The implications of the study suggest that improving discipline should be prioritized to enhance overall employee performance.